A novel analysis of planar dipole antenna arrays in free space with the multiple-sweep method of moments - Kawdungta, Supakit; Phongcharoenpanich, Chuwong; Torrungrueng, Danai (My University, 2011)
In this article, the multiple-sweep method of moments is employed to effectively analyze electromagnetic radiation problems of planar dipole antenna arrays in free space. Two sweeping procedures (row and sawtooth sweeps) associated with the multiple-sweep method of moments are proposed, and their obtained results are compared with those computed using the conventional conjugate gradient method. Two examples of a 5 × 5 uniform and a 24 × 24 nonuniform planar dipole antenna arrays are considered. It is found that the multiple-sweep method of moments with the sawtooth sweep overcomes the inefficiency of the original multiple-sweep method of moments with the row sweep, because the associated number of unknowns for each section of the row sweep is relatively large. In addition, the current distributions and radiation patterns computed by using the multiple-sweep method of moments with the sawtooth sweep are in excellent agreement with those obtained from the standard method of moments. Thus, the multiple-sweep method of moments with the sawtooth sweep is efficient and accurate for electrically large problems of planar dipole antenna arrays in free space. Copyright © Taylor & Francis Group, LLC.
Keywords: conjugate gradient method; multiple sweep method of moments; planar dipole antenna array